Behavioral economic analysis of demand for fuel in North America. Issue 3 (12th August 2013) - Reed, Derek D.; Partington, Scott W.; Kaplan, Brent A.; Roma, Peter G.; Hursh, Steven R.
<x xml:space="preserve">Abstract</x> Emerging research clearly indicates that human behavior is contributing to climate change, notably, the use of fossil fuels as a form of energy for everyday behaviors. This dependence on oil in North America has led to assertions that the current level of demand is the social equivalent to an "addiction." The purpose of this study was to apply behavioral economic demand curves—a broadly applicable method of evaluating relative reinforcer efficacy in behavioral models of addiction—to North American oil consumption to examine whether such claims of oil addiction are warranted. Toward this end, we examined government data from the United States and Canada on per capita energy consumption for transportation and oil prices between 1995 and 2008. Our findings indicate that consumption either persisted or simultaneously increased despite sharp increases in oil price per barrel over the past decade.